An Analysis of Indonesia’s 2013 EFL Curriculum and Turkey’s National English Language Curriculum for Secondary Schools - Suci Noer Wulan Sari; Niken Anastasia Kusuma Wardani (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Indonesia and Turkey have experienced educational reforms for decades, for instance in constructing EFL curriculum. Educational reforms could be done to address a certain problem encountered by a nation and to better the quality of education. Therefore, there emerged a need to analyse the EFL curricula designed for secondary schools in both countries to identify the commonalities and differences considered for a better improvement in education quality. Thus, the present study was aimed at analysing Indonesia’s 2013 EFL Curriculum and Turkey’s National English language Curriculum for secondary schools: the rationale, aims and organization (instructional design, instructional materials, and assessment). The study employed a qualitative descriptive design using document analysis to analyse some curricula documents. The findings revealed the commonalities lie in learner-centeredness view and the main goal of EFL curriculum. However, the differences lie in the instructional design, materials, and assessment. Given that Indonesia may adopt technology-enhanced assessment for a better assessment. It is suggested for further studies to employ interviews and surveys with teachers and students to gain more data.